(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2017)
In this paper we aim to search, starting from the iconographic repertory, which was the image of Patagonian aboriginal women constructed through the almost exclusive male point of view. These men were those who visited or take care of the inhabitants of this territory since its discovery. We speak of “Construction” because we supposed that the images are transmitters, conscious or unconscious, of our ideas. We understand that those who produced them registered their particular perception of the reality, that is to say, they expressed in the images their own look of the world embedded in the social and cultural frame of the time. To achieve this objective we will take some cases that can exemplify this process. We will also take in account the congruence between the written text, the visual text and the material record.